The Radiological Management of Pseudoaneurysms Complicating Pancreatitis - De Rosa, Antonella; Gomez, Dhanwant; Pollock, John G; Bungay, Peter; De Nunzio, Mario; Hall, Richard I; Thurley, Peter (JOP. Journal of the Pancreas, 2012)
Context Pseudoaneurysms associated with pancreatitis are rare, and bleeding pseudoaneurysms are associated with a high mortality. Objective The aim of this study was to report the outcomes of endovascular and percutaneous therapy in the management of pseudoaneurysms secondary to pancreatitis. Patients Patients who underwent angiography for pseudoaneurysms associated with pancreatitis from 2005 to 2011 were identified from the angiography database. Main outcome measures Patient demographics, clinical presentation, radiological findings, treatment, and outcomes were retrospectively reviewed. Results Nineteen pseudoaneurysms associated with pancreatitis in 13 patients were identified. The diagnosis of a pseudoaneurysm was made by computerised tomography angiography in seven patients, followed by portal venous phase contrast enhanced CT (n=4), duplex ultrasound (n=1) and angiography (n=1). At angiography, coil embolisation was attempted in 11 patients with an initial success rate of 82% (n=9). One patient underwent successful embolisation with percutaneous thrombin injection. The recurrence rate following initial successful embolisation was 11% (n=1). There were no episodes of re-bleeding following embolisation but re-bleeding following thrombin injection was observed in one case. The morbidity and mortality rate in the 12 patients that were successfully treated was 25% (n=3) and 8% (n=1), respectively. All 12 patients that were successfully treated demonstrated radiological resolution of their pseudoaneurysms, with a median follow-up of 20 months. Conclusion Endovascular embolisation is a suitable first-line management strategy associated with low recurrence rates. The role of percutaneous thrombin injection is yet to be defined. Image: Arterial phase computed tomography demonstrates a small pseudoaneurysm.